THE EFFECTIVENESS OF ELECTRONIC HUMAN DEVELOPMENT WORKER (E-HDW) IN MANAGING STUNTING RATES IN RANGKAH KIDUL VILLAGE, SIDOARJO DISTRICT - Aisyah, Nur; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to describe and analyze the effectiveness of Electronic Human Development Worker (E-HDW) in managing stunting rates in Rangkah Kidul Village, Sidoarjo District through three main indicators, including E-leadership, Information Network Infrastructure, and Information Management. This e-HDW was developed to assist human development cadres (KPM) in recording, monitoring, and reporting stunting target data. Method: This study uses a qualitative method with a descriptive type. Data collection techniques are carried out through observation activities in the field, interviews with related parties, and collection of documents as information support materials. Result: As a result of the research on the E-leadership indicator, the village government has provided active support through training and provision of facilities for the use of E-HDW. The information network infrastructure is considered quite adequate, although there are still technical glitches such as server problems and system maintenance. In the information management indicators, the data in the E-HDW is stored and managed quite well, but information related to children's growth and development has not been presented completely and is not as accurate as data from the health center. Novelty: The novelty in this study focuses on the direct application at the village level as well as findings regarding the difference between child growth and development data displayed by E-HDW and manual health data from health centers, which can be used as evaluation material for future development, as well as providing a real picture of the challenges of applying digital technology in handling stunting in villages.